Proposed Marketing Strategy for the Sustainability of Biomass Producer Companies (PT XYZ Case Study) - Aulia Rizki Utami; Bustanul Arifin Noer (Publikasi Indonesia, 2024)
PT XYZ is a biomass production company established in 2021, dedicated to sustainable biomass solutions, positioning itself at the forefront of an industry with significant growth potential given the global urgency for clean energy solutions. Despite operating in a high-growth potential sector, PT XYZ experienced stagnation and even a decline in product sales in 2023. To understand the root causes and formulate effective solutions, this study employs various analytical methods, including the Internal Factor Evaluation (IFE) Matrix and the External Factor Evaluation (EFE) Matrix to assess the internal and external factors affecting the company's performance. The Internal-External (IE) Matrix and SWOT Matrix were then used to match these factors and develop various strategic alternatives. Finally, the Quantitative Strategic Planning Matrix (QSPM) was used to objectively evaluate the strategic alternatives and generate optimal marketing strategy recommendations for PT XYZ. Based on the analysis using the IFE and EFE matrices, PT XYZ is positioned in the grow and build quadrant with an IFE score of 3.29 and an EFE score of 3.20. Through SWOT analysis, seven alternative marketing strategies were identified. Subsequently, QSPM analysis prioritized these strategies, with obtaining SVLK certification as the top priority, followed by increasing awareness and branding, developing innovation and product diversification, expanding into new markets, enhancing human resources in sales and marketing, increasing production capacity, and improving education and awareness about renewable energy.